Impact of Training on Tenchers’ Productivity in Allmosho Local Government Secondary Schools, Lngos State - ALAO, Busnyo Oluwabukola; OBAFEMI, Oyemade Mark (International Journal of Educational Management, 2025)
The importance of training on the productivity of teachers cannot be over emphasized and the need for improved productivity in every organisation has become universally accepted which depends on the effectiveness of the training given to the teachers. Being a competent and well-performing teacher is one of the most important r e sources in any educational institution. The teacher is considered the professional agent and the most directly responsible person in the process of learning which makes him the one in charge of helping students learn and benefit or suffer from the quality of his teaching. However, the teacher and the quality of his/her teaching are always under discussion and receive prevalent importance in education. In today’s changing commercial environment and rapid globalization, it is obvious that secondary schools are increasingly concerned with competitive edge, exceptional performance and sustainable profits.It is also believed that without healthy, engaged and productive teachers, it is very tough to achieve the aims and objectives of the school. T eachers’ professional training and professional development is a necessary ingredient to support innovative and beneficial teaching. The aim of this paper is to highlight the importance of training given to teachers’ training in improving and boosting the quality of education in the Nigerian context. However, teacher training is one of the important management topics that has received significant research attentions from several scholars and considered as a primary mechanism to enhance the success in the school.